A FLEMISH VENUS IN MILAN: GASPAR VAN WEERBEKE'S MISSA O VENUS BANT. (October 2019) - Pavanello, Agnese
Abstract: The mass O Venus bant by Gaspar van Weerbeke enjoyed notable fame and diffusion, as shown by the considerable number of surviving copies. This study formulates a new hypothesis about the origin of the mass. An examination of the transmission of the mass suggests a new scenario for its composition in Milan in connection with a major political event: the alliance of the Duchy of Milan and the Duchy of Savoy with Charles the Bold in 1475. The choice of a Flemish cantus firmus is thus linked to a specific occasion related to the region in which the melody originated. Since some compositional elements can be read as intentional references to the L'Homme armé tradition, the specific context proposed for the performance of the polyphonic cycle seems particularly plausible because it can be linked to the court of Burgundy both in terms of historical and political events, as well as on the compositional and symbolic level. Finally, the possibility that Gaspar van Weerbeke was the initiator of the musical tradition of polyphonic settings of the chanson O Venus bant is explored.